2006
DOI: 10.1080/15287390600751322
|View full text |Cite
|
Sign up to set email alerts
|

Familial Characteristics of Kidney-Yang Deficiency and Cold Syndrome

Abstract: Family investigation is a reliable model to study the effects of both genetic and environmental factors on human health. This article studies kidney-yang deficiency syndrome and cold syndrome through family investigation and cDNA microarray technology, exploring the effects of both genetic and environmental factors on the health of family members. Particularly, these two syndromes were first assessed by the accumulated clinical scores measured by 40-item scoring tables among 15 family members. The family patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…8,12,14 Consequently, KDS transcriptome obtained from our experiments revealed that KDS patients suffer from extensive impairments involving large parts of the mass-energy-information carrying network, while the low energy expenditure is merely one of the distinctive features, yet a marked symptom, in KDS patients.…”
Section: Kds Transcriptome Focuses On Energy Metabolismmentioning
confidence: 97%
See 2 more Smart Citations
“…8,12,14 Consequently, KDS transcriptome obtained from our experiments revealed that KDS patients suffer from extensive impairments involving large parts of the mass-energy-information carrying network, while the low energy expenditure is merely one of the distinctive features, yet a marked symptom, in KDS patients.…”
Section: Kds Transcriptome Focuses On Energy Metabolismmentioning
confidence: 97%
“…One of the KDS pedigrees live in Xingxin town of Peng Zhou City, Sichuan Province, China, and have been intensively studied. 6,[8][9][10] Another family, which has 17 KDS patients and lives around Chengdu, Sichuan, China, was chosen as the subject for this present study (Fig. 1).…”
Section: Questionnaire and Tcm Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have been few investigations that have focused on genetic alterations that might correlate with this disease. Wang et al [1] suggested that the cause and progression of KDS involves not only environmental factors but genetic elements as well. Pan et al [2] analyzed the transcriptomic patterns of KDS subjects utilizing microarrays.…”
Section: Introductionmentioning
confidence: 99%
“…There have been some studies not only about the gene expression profiles in kidney-Yang deficiency (Wei et al, 2011) but also about the non-inflammatory and non-liquefied semen as deficiency Yang symptoms . In studies of kidney-Yang deficiency syndrome, it was closely related to the cold syndrome through family investigation and cDNA microarray technology, exploring the effects of both genetic and environmental factors on the health of family members (Wang et al, 2006).…”
Section: Deficiency Of Yang (陽)mentioning
confidence: 99%